2006
DOI: 10.1108/02683940610690213
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age differences in occupational stress and professional burnout between primary and high‐school teachers in Greece

Abstract: Purpose -To identify the specific sources of occupational stress and the professional burnout experienced by teachers working in Greek primary and secondary schools. A special emphasis is given to gender and age differences. Design/methodology/approach -A cross-sectional design was used. Two self-report measures were administered to a sample of 493 primary and secondary school teachers, a self-report rating scale of specific occupational stressors and the Maslach Burnout Inventory (education version). Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
201
8
53

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(287 citation statements)
references
References 17 publications
25
201
8
53
Order By: Relevance
“…20 Davidson et al found that female managers are under much more pressure than their male counterparts, and Antoniou et al found that female teachers experienced significantly higher levels of occupational stress compared to their male counterparts. 22 In our study female employees experienced lesser level of stress than males, may be as they were engaged in less demanding tasks at work than men and they often had lesser nonwork demands.…”
mentioning
confidence: 74%
“…20 Davidson et al found that female managers are under much more pressure than their male counterparts, and Antoniou et al found that female teachers experienced significantly higher levels of occupational stress compared to their male counterparts. 22 In our study female employees experienced lesser level of stress than males, may be as they were engaged in less demanding tasks at work than men and they often had lesser nonwork demands.…”
mentioning
confidence: 74%
“…Otras investigaciones han concluido que entre el 60% y el 70% de los profesores mostró repetidamente síntomas de estrés (Antoniou et al, 2006). También, el 35.4% y el 7.7% de los orientadores de centros de enseñanza secundaria percibió, respectivamente, un nivel de estrés alto y muy alto (Guerrero y Rubio, 2008;Rubio, 2003).…”
Section: Discussionunclassified
“…Burke (1988) agrupa los factores de riesgo en las siguientes seis categorías: entorno físico, rol, estructura organizativa y características del puesto de trabajo, relaciones con los demás, desarrollo de la carrera profesional, y conflicto entre vida personal y vida laboral. Recientemente, Antoniou et al (2006) indican que las condiciones específicas que determinan el estrés en el trabajo abarcan los factores exógenos (i.e., condiciones de trabajo deficientes, sobrecarga de trabajo, la falta de colaboración) o las presiones endógenas (i.e, características de personalidad). Posteriormente, Poloski y Bogdanovic (2007) en base a una exhaustiva revisión de la literatura, afirmaron que si añadimos la complejidad y la turbulencia del entorno contemporáneo en conjunto, las causas del estrés laboral se pueden agrupar en dos grandes grupos: (1) los factores relacionados con el trabajo, con tres grandes subgrupos relacionados con el entorno, la organización y el puesto de trabajo respectivamente, y (2) los relacionados con el individuo, que son consecuencia de distintas características o circunstancias de la vida.…”
Section: Marco Teóricounclassified